Pelatihan Pengolahan Sampah Plastik: Upaya Membangun Karakter Peduli Lingkungan bagi Anak-Anak - Syarifah Farissi; Nurhamida; Hasna Humaira; Nurul Qolbiya (Rengganis Jurnal Pengabdian Masyarakat, 2025)
Plastic waste is a major environmental problem because it is a type of waste that is very difficult to decompose. The lack of educational activities involving children in plastic waste processing results in low awareness and limited involvement in efforts to maintain environmental sustainability. This leads to a lack of environmental responsibility among the younger generation, who should be the agents of change for a better future. The purpose of this community service activity is to provide training to children in Gampong Bakoy, Ingin Jaya District, Aceh Besar, regarding the impact of plastic waste on the environment and creative ways to process it. Through this training, it is hoped that children can develop an enviromentally conscious character from an early age. This activity was attended by children from TPA Pelita Hati, aged 5 to 12 years. The activity was carried out over two days. Based on the evaluation results, data showed an increase in understanding of the impact, types, and classification of waste (98%), an increase in enviromentally conscious behavior (97%), and an increase in children’s creativity in making products from plastic waste (96%).